1998
DOI: 10.1074/jbc.273.16.9852
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-associated Mts1 (S100A4) Protein Modulates Protein Kinase C Phosphorylation of the Heavy Chain of Nonmuscle Myosin

Abstract: Mts1 protein (S100A4 according to a new classification) has been implicated in the formation of the metastatic phenotype via regulation of cell motility and invasiveness. Previously we have demonstrated that Mts1 protein interacted with the heavy chain of nonmuscle myosin in a calcium-dependent manner. To elucidate the role of the Mts1-myosin interaction, we mapped the Mts1-binding region on the myosin heavy chain molecule. We prepared proteolytically digested platelet myosin and a series of overlapped myosin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 47 publications
(62 reference statements)
1
104
0
2
Order By: Relevance
“…More importantly, a completely novel finding is now made that the presence of S100A1 antagonizes a major biological function of S100A4, that of the induction of metastasis in vivo and associated properties in cultured cells. S100A4 interacts with, and inhibits the self-association of rNMMHCIIA (Kriajevska et al, 1994;Ford and Zain, 1995), and it has been suggested that S100A4 affects the phosphorylation of a NMMHCIIA fragment by protein kinase C and casein kinase 2 in vitro (Kriajevska et al, 1998. When tested in vitro, S100A1 significantly and specifically reversed the inhibitory effects of S100A4 on both the self-assembly of a recombinant fragment of NMMHCIIA and its phosphorylation by protein kinase C. S100A1 itself showed no effect on the self-assembly and phosphorylation by PKC of the NMMHCIIA in vitro, suggesting strongly that the effect of S100A1 is not a direct one, but acts by affecting S100A4 function.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, a completely novel finding is now made that the presence of S100A1 antagonizes a major biological function of S100A4, that of the induction of metastasis in vivo and associated properties in cultured cells. S100A4 interacts with, and inhibits the self-association of rNMMHCIIA (Kriajevska et al, 1994;Ford and Zain, 1995), and it has been suggested that S100A4 affects the phosphorylation of a NMMHCIIA fragment by protein kinase C and casein kinase 2 in vitro (Kriajevska et al, 1998. When tested in vitro, S100A1 significantly and specifically reversed the inhibitory effects of S100A4 on both the self-assembly of a recombinant fragment of NMMHCIIA and its phosphorylation by protein kinase C. S100A1 itself showed no effect on the self-assembly and phosphorylation by PKC of the NMMHCIIA in vitro, suggesting strongly that the effect of S100A1 is not a direct one, but acts by affecting S100A4 function.…”
Section: Discussionmentioning
confidence: 99%
“…A recombinant C-terminal peptide of human myosin heavy chain named Hmyo4-3B (1762-1961 amino acids) was isolated and purified as described (Kriajevska et al, 1998). Human recombinant S100A12 was isolated and purified as described (Mikkelsen et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The up-regulation of nonmuscle myosin heavy chain and a putative phosphorylated form of myosin heavy chain (putative protein kinase C substrate by prediction rules) in the LPSexposed PMN (Table IV) is of uncertain significance; myosin has been implicated in multiple functions in the PMN, including locomotion, fluid pinocytosis, and phagocytosis (58). Of interest, however, S100A4 (down-regulated, Table II) has been reported to regulate cytoskeletal dynamics by inhibiting protein kinase C-mediated phosphorylation of nonmuscle myosin heavy chain (59). LPS induction of stathmin phosphorylation (Table IV and Fig.…”
Section: Table V Analysis Of Ph 55-67 Two-dimensional Page Gelsmentioning
confidence: 99%